On‐Demand Removable Self‐Healing and pH‐Responsive Europium‐Releasing Adhesive Dressing Enables Inflammatory Microenvironment Modulation and Angiogenesis for Diabetic Wound Healing (Small 3/2023). Issue 3 (18th January 2023) - Fu, Meimei; Zhao, Yitao; Wang, Yue; Li, Yue; Wu, Min; Liu, Qi; Hou, Zhiguo; Lu, Zhihui; Wu, Keke; Guo, Jinshan
Abstract : Diabetic Wound Healing In article number 2205489, Jinshan Guo, Keke Wu, and co‐workers develop an on‐demand removable, pH‐responsive europium‐releasable and photothermal antimicribal adhesive dressing for diabetic wound healing. The adhesive provides convenient non‐invasive wound closure, enables in‐time painless dressing change upon mixing with borax solution, and smoothly connects inflammatory microenvironment modulation, angiogenesis promotion and effective extracellular matrix production for accelerated diabetic wound healing.